Reduced vitamin D-induced cathelicidin production and killing of Mycobacterium tuberculosis in macrophages from a patient with a non-functional vitamin D receptor: A case report - Al-Jaberi, Fatima A. H.; Crone, Cornelia Geisler; Lindenstrøm, Thomas; Arildsen, Nicolai Skovbjerg; Lindeløv, Emilia Sæderup; Aagaard, Louise; Gravesen, Eva; Mortensen, Rasmus; Andersen, Aase Bengaard; Olgaard, Klaus; Hjaltelin, Jessica Xin; Brunak, Søren; et al. (Frontiers in Immunology, 2022)
Tuberculosis (TB) presents a serious health problem with approximately a quarter of the world’s population infected with Mycobacterium tuberculosis (M. tuberculosis) in an asymptomatic latent state of which 5–10% develops active TB at some point in their lives. The antimicrobial protein cathelicidin has broad antimicrobial activity towards viruses and bacteria including M. tuberculosis. Vitamin D increases the expression of cathelicidin in many cell types including macrophages, and it has been suggested that the vitamin D-mediated antimicrobial activity against M. tuberculosis is dependent on the induction of cathelicidin. However, unraveling the immunoregulatory effects of vitamin D in humans is hampered by the lack of suitable experimental models. We have previously described a family in which members suffer from hereditary vitamin D-resistant rickets (HVDRR). The family carry a mutation in the DNA-binding domain of the vitamin D receptor (VDR). This mutation leads to a non-functional VDR, meaning that vitamin D cannot exert its effect in family members homozygous for the mutation. Studies of HVDRR patients open unique possibilities to gain insight in the immunoregulatory roles of vitamin D in humans. Here we describe the impaired ability of macrophages to produce cathelicidin in a HVDRR patient, who in her adolescence suffered from extrapulmonary TB. The present case is a rare experiment of nature, which illustrates the importance of vitamin D in the pathophysiology of combating M. tuberculosis.